Devoir 2 C
Devoir 2 C
Devoir 2 C
Sébastien Roy
February 20, 2012
fZ (z) = FX (z) − FX (z − 1)
1
GEL7060 – (Communications numériques avancées) 2
but
fY (y) = u(y) − u(y − 1),
leading to Z 1
fZ (z) = fX (z − α)dα.
0
Letting u = z − α and therefore du = −dα, we have
Z z−1
fZ (z) = − fX (u)du
Z zz
= fX (u)du
z−1
Z z Z z−1
= fX (u)du − fX (u)du
−∞ −∞
= FX (z) − FX (z − 1).
− 14 1 f
4
#1
ej2πf k
"
4
=
j2πk − 14
jπk jπk
e− e− 2
2
=
j2πk
!
sin(πk/2) 1 k
= = sinc .
πk 2 2
and we have
∞
X ∞
X
RY Y [k] = h[m]h[l]RXX [k + m − l]
m=−∞ l=−∞
∞ ∞
1 k+m−l
X X
= (δ[m] + δ[m − 4]) (δ[l] + δ[l − 4]) sinc
m=−∞ l=−∞
2 2
∞
1 k−l k+4−l
X
= (δ[l] + δ[l − 4]) sinc + sinc
2 l=−∞ 2 2
1 k k+4 k−4 k
= sinc + sinc + sinc + sinc
2 2 2 2 2
k 1 k−4 k+4
= sinc + sinc + sinc .
2 2 2 2
* ∞ +
X
µS = A[k]g(t − kT )
k=−∞
∞
X
= hA[k]i g(t − kT )
k=−∞
X∞
= µA g(t − kT ).
k=−∞
In the strict sense, we cannot reduce more than this given the information
that we have.
Observing RAA [k], we see that it is possible that A[k] is bipolar of ampli-
tude √12 with equally-likely pulses. However, we cannot confirm this. If it
were true, then we would have µS = µA = 0.
1 ∗
RSS (t, t + τ ) = hS (t)S(t + τ )i
2*
∞ ∞
+
1 X ∗
X
= A [k]g(t − kT ) A[l]g(t + τ − lT )
2 k=−∞ l=−∞
∞ ∞
1 X
hA∗ [k]A[l]i g(t − kT )g(t + τ − lT )
X
=
2 k=−∞ l=−∞
∞
X ∞
X
= RAA [l − k]g(t − kT )g(t + τ − lT )
k=−∞ l=−∞
∞
1 1
X
= g(t) − (g(t − T ) + g(t + T )) g(t + τ − lT )
l=−∞ 2 4
GEL7060 – (Communications numériques avancées) 6
1
= µA .
2
1 1
−1−n2 − 2.5y
fY (y) = y e .
Γ(n2 )2.5n2
Z1
Then, using the Mellin convolution, we compute the PDF of X = Z2 = Z1 Y :
Z ∞
x 1
fX (x) = fY fZ1 (a) da
0 a a
x −1−n2
an1 −1 e−a
Z ∞
a
= a
e− 2.5x da
0 Γ(n2 )2.5n2 Γ(n1 )a
1 ∞ Z
1
= an1 +n2 −1 e−a(1+ 2.5x ) da
Γ(n1 )Γ(n2 )2.5n2 x1+n2 0
n1 +n2
1 5x
= Γ(n1 + n2 )
Γ(n1 )Γ(n2 )2.5n2 x1+n2 5x + 2
xn1 −1
= n1 +n2 u(x).
B(n1 , n2 )2.5n2 x + 25
GEL7060 – (Communications numériques avancées) 8
A1 + A2 + A3 + A4 = 1,
−5A1 − 6A2 − 2A3 − 4.5A4 = 0,
−6.25A1 − (6.25 + 5)A2 − A3 − (1 + 5)A4 = 0,
6.25A2 + 2.5A4 = 0,
GEL7060 – (Communications numériques avancées) 9
A1 = 0.4444,
A2 = 1.4815,
A3 = 2.7778,
A4 = −3.7037.
Hence, we have
A3 − x A4 − x
fY (y) = A1 xe−x + A2 e−x + 2
xe 2.5 + e 2.5
2.5 2.5
A3 A4
x
= (A1 x + A2 ) e−x + 2
x + e− 2.5 .
2.5 2.5